THE IMPLEMENTATION OF CHARACTER EDUCATION IN FORMING STUDENT’S MORALS AND SPIRITUALITY - Eriyanto Eriyanto; Abdulwaris Chelong bin Zakariya (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2024)
Madrasah Aliyah Hidayatullah is a madrasah located in the Abu Zairi Bondowoso Islamic Boarding School. This Islamic boarding school is known for its high religious nuances by the surrounding community. So, these characteristics are also found in Madrasah Aliyah Hidayatullah which is in it. This research was carried out to uncover the character education applied in the institution. The method used to reveal this is qualitative-descriptive by making managers, teachers, and students as informants and their daily life behaviors at school and related documents. The results of this study show that character education at Madrasah Aliyah Hidayatullah is a typical character education of Islamic boarding schools which is standardized by the school as Standard Operating Procedures (SOP). There are 6 (six) programs contained in the SOP, namely Program 1A, Program 13S, Program 6R, Program 4O, 3B, and SATFA Program.